2022
DOI: 10.1002/cncy.22643
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an RNA sequencing–based classifier for medullary thyroid carcinoma on thyroid FNA

Abstract: This commentary describes the development and validation of the Afirma RNA sequencing–based classifier for medullary thyroid carcinoma (MTC). The importance of the early diagnosis of MTC is discussed along with the limitations of cytomorphology alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…We performed a validation study of the IMTCGS at our institution that found similar promising results. 8 Of our 87 MTC cases, 18.4% (n = 16) were high grade. These high-grade MTCs had decreased disease-free survival (DFS), DMFS, DSS, and OS compared to low-grade MTCs.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…We performed a validation study of the IMTCGS at our institution that found similar promising results. 8 Of our 87 MTC cases, 18.4% (n = 16) were high grade. These high-grade MTCs had decreased disease-free survival (DFS), DMFS, DSS, and OS compared to low-grade MTCs.…”
Section: Introductionmentioning
confidence: 79%
“…In our validation study of the IMTCGS on surgical resection material, of the eight high-grade MTCs with increased mitoses (five or greater per 2 mm 2 ), only four showed a concurrent increase in Ki67 PR. 8 On the other hand, only two cases showed an increased Ki67 PR in the absence of an increased mitotic rate. In the current study, we attempted to determine how predictive the mere presence of mitotic figures in MTC cytology might be of tumor grade.…”
Section: F I G U R E 1 Scatterplot Depicting the Correlation Between ...mentioning
confidence: 93%
“…The initial training and discovery cohort was based on 300 patients with MTC from five academic centres (Royal North Shore Hospital [RNSH], Sydney, Australia: n = 58; Institut Gustave Roussy [IGR], Villejuif, France: n = 70; Memorial Sloan Kettering Cancer Center [MSKCC], New York, NY: n = 68; University of Bologna Medical Center [BO], Bologna, Italy: n = 64; and Brigham and Women's Hospital [BWH], Boston, MA: n = 40) which had previously contributed to the IMTCGS study 9 . In addition to k ‐fold validation (described below), as an independent validation cohort we included data from an additional 87 MTC patients from Emory University Midtown Hospital, Atlanta, GA 18 . Although patients from these cohorts were included in prior studies, 7,8,9,18,19 prognostic factors were independently assessed, and survival data updated for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The predictive model was externally validated using a separate cohort of patients with MTC ( n = 87) from Emory University Midtown Hospital to test the model's generalizability. The clinical and pathological features of this cohort have been previously reported, 18 but were not used in any way for model training. ROC curves for the two cohorts are illustrated in Figure S8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation